Engineering the crystallinity of tin disulfide deposited at low temperatures. Issue 59 (3rd June 2016) - Ham, Giyul; Shin, Seokyoon; Park, Joohyun; Lee, Juhyun; Choi, Hyeongsu; Lee, Seungjin; Jeon, Hyeongtag
Abstract : We report here that SnS2 films deposited at 150 °C and annealed at below 350 °C have good potential for using 2D SnS2 in flexible electronic devices. Abstract : Tin disulfide (SnS2 ), which exhibits a two-dimensional (2D) layered structure, is considered to be a promising channel material for thin film transistors because of its high electrical performance and low temperature processibility. In this work, we deposited crystalline SnS2 at 150 °C using atomic layer deposition (ALD) which is compatible with current electronic device processing methods. And then, crystalline SnS2 films were annealed to investigate the change in crystallinity. We carried out sulfur annealing of the SnS2 films at temperatures of 250, 300 and 350 °C. The effects of sulfur annealing were investigated in a mixed gas atmosphere of 100 sccm argon (Ar) and 5 sccm hydrogen (H2 ). SnS2 samples were examined using XRD, TEM, XPS, UV-vis and PL. The crystallinity of the SnS2 films after annealing was improved, and its grain size became larger compared with the as-deposited SnS2 film. We also observed a clear two dimensional layered structure of SnS2 using high resolution TEM. The change in the optical properties of the SnS2 films was observed using UV-vis and PL.